Thermal properties of open-celled aluminum foams prepared by two infiltration casting methods - Wang, Hui; Zhou, Xiang-yang; Long, Bo; Wen, Kang; Yang, Tao (Journal of Central South University, 2014)
Contrastive research was carried out to study the thermal properties of open-celled aluminum foams prepared by counter-gravity infiltration casting system and the traditional process respectively. The experimental results show that the thermal conductivity coefficients of aluminum foams prepared by two different infiltration methods have similar increasing trend with the increase of particle size; along with the reducing porosity, the thermal conductivity coefficients will be enhanced oppositely. However, with the same particle size, the open-celled aluminum foam prepared by the former method has a higher thermal conductivity coefficient obviously. It is largely because that the sample prepared by counter-gravity infiltration casting has a lower void content and better dense crystallization of metal-matrix after the constant pressure process.